2013
DOI: 10.1111/cge.12325
|View full text |Cite
|
Sign up to set email alerts
|

Pellagra‐like condition is xeroderma pigmentosum/Cockayne syndrome complex and niacin confers clinical benefit

Abstract: An extremely rare pellagra-like condition has been described, which was partially responsive to niacin and associated with a multisystem involvement. The condition was proposed to represent a novel autosomal recessive entity but the underlying mutation remained unknown for almost three decades. The objective of this study was to identify the causal mutation in the pellagra-like condition and investigate the mechanism by which niacin confers clinical benefit. Autozygosity mapping and exome sequencing were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…This finding also suggests that viability may be predicated on the presence and partial functionality of XPG. Two other studies also found that the most severe cases of XP-CS in their cohort resulted from severely truncated XPG proteins that were suspected to be nonfunctional [24, 63], compared with a milder case in a compound heterozygous patient with one partially functional copy of the XPG gene. Again, these findings suggest that partial functionality in at least one allele may result in a milder phenotype.…”
Section: Discussionmentioning
confidence: 97%
“…This finding also suggests that viability may be predicated on the presence and partial functionality of XPG. Two other studies also found that the most severe cases of XP-CS in their cohort resulted from severely truncated XPG proteins that were suspected to be nonfunctional [24, 63], compared with a milder case in a compound heterozygous patient with one partially functional copy of the XPG gene. Again, these findings suggest that partial functionality in at least one allele may result in a milder phenotype.…”
Section: Discussionmentioning
confidence: 97%
“…This finding also suggests that viability may be predicated on the presence and partial functionality of XPG. Two other studies also found that the most severe cases of XP-CS in their cohort resulted from severely truncated XPG proteins that were suspected to be nonfunctional [24,63], compared with a milder case in a compound heterozygous patient with one partially functional copy of the XPG gene. Again, these findings suggest that partial functionality in at least one allele may result in a milder phenotype.…”
Section: Genes and Phenotypementioning
confidence: 93%
“… c.[?] 9 mo 6.5 y Y N Y Y Y Y Y Y [ 157 , 158 ] XP72MA p.[Glu727*] c.[2179G>T] p.[Trp814Ser] c.[2441G>C] 7 y ND Y N ND Y ND ND Y Y [ 155 ] Patient case 16 p.[Glu734_Thr1186 delins2*] c.[2200-10C>G] 4.3 y ND Y N Y Y N Y Y Y [ 163 ] Patient case 1 p.[Asp798Tyr] c.[2392G>T] 3 y 6.5 y Y N Y Y ND Y Y ND [ 164 ] Patient case 2 c p.[Asp798Tyr] c.[2392G>T] …”
Section: Xpg and Human Diseasementioning
confidence: 99%